Bilateral abducens nerve palsy from post-spinal-anesthesia-induced bilateral chronic subdural hematoma: case report - Shiferaw, Mestet Yibeltal; T/Mariam, Tsegazeab Laeke; Aklilu, Abenezer Tirsit; Shumbash, Kibruyisfaw Zewudie; Akililu, Yemisirach Bizuneh; Worku, Bethelhem Yishak; Ayele, Mengistu (Frontiers in Anesthesiology, 2023)
Background A chronic cranial subdural hematoma arising after post-spinal anesthesia is a rare but serious and life-threatening complication of spinal anesthesia. It usually mimics the typical post-spinal-anesthesia headache or post-dural-puncture headache, potentially masking its detection. Abducens nerve palsy tends to occur in chronic subdural hematoma of post-dural-puncture etiology rather than in cases attributed to other causes of subdural hematoma. Preferential damage to the abducens nerve is frequent and can be attributed to its anatomic course because the abducens nerve runs in the direction of the typical caudad displacement of the brain related to intracranial hypotension. Observation Here, we present a report on the clinical presentation, pathogenesis, and management of two cases that developed bilateral abducens nerve palsy following post-spinal anesthesia administered for cesarean sections due to obstetric indications. Lesson Post-spinal-anesthesia-induced chronic subdural hematoma, although a rare, life-threatening complication, must be differentiated from post-spinal-anesthesia headache and treated surgically. Cranial nerve palsy (more commonly called abducens nerve palsy) is more common in post-spinal-anesthesia-induced subdural hematoma than subdural hematomas of other etiologies as the cerebrospinal fluid brain cushioning is partly lost. Cranial nerve palsies resolve in most cases if surgery is performed in a timely manner.